Sarcoidosis mimicking metastatic papillary thyroid cancer - Salih, Abdulwahid M. (Int J Surg Case Rep, 2015)
INTRODUCTION: Sarcoidosis is a multisystemic, idiopathic disease. It has a highly variable clinical course. It has been reported to present in association with malignancy. Coexistence of sarcoidosis and thyroid cancer is rarely reported in the literature. PRESENTATIOIN OF THE CASE: We present a case with neck swelling for 3 months, and symmetrical painless thyroid enlargement without fixation to deep tissues of the neck. Multiple nodules on the both thyroid lobes, hard irregular, grade two goiter with lymphadenopathy all over anterior neck compartments. Fine needle aspiration cytology was done under ultrasound guide from right thyroid nodule and showed papillary thyroid carcinoma. Excisional biopsy of the neck lymphnode showed picture typical for sarcoidosis. DISCUSSION: Most researchers believe that patients with pulmonary sarcoidosis are predisposed to develop malignancies, less than a dozen of cases are reported in the literature to be associated with PTC with a very wide range of presentations and clincal coarses. An interesting finding of our case is that in contrast to what is reported, both diseases were not known by the physician until the time of presentation. CONCLUSION: Cervical lymphadenopathy in association with goiter could be metastasis, sarcoidosis or mixed, therefore should be seperately biopsied.